2020
DOI: 10.1001/jamaophthalmol.2019.4511
|View full text |Cite
|
Sign up to set email alerts
|

SETD2 Mutation in an Aggressive Optic Nerve Glioma

Abstract: exotropia in Rembrandt's self-portraits, because the portrayed deviation did not increase over his lifetime 4 (exotropia usually increases over time). In addition, there is no historical record of such misalignment.Three of Leonardo's 4 paintings and sketches mentioned by Tyler 2 display exotropia, suggesting that Leonardo may also have had strong eye dominance. Curiously, Tyler also mentions 2 sculptures attributed to Leonardo's master and hypothesizes that Leonardo modeled for these. While the sculptures hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The pathogenic factors of this disease are relatively complex. Under the interaction of congenital genetic factors and environmental carcinogenic factors, the level of genetic and epigenetic material of cells has undergone cancer mutation [ 2 ]. These mutations drive cells to continuously enter the cell cycle, avoid immune suppression, apoptosis, and mitosis, and contact suppression of cell growth, etc., and abnormal energy metabolism, hypoxia, and necrosis corresponding to continuous cell growth also induce changes in tumor angiogenesis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic factors of this disease are relatively complex. Under the interaction of congenital genetic factors and environmental carcinogenic factors, the level of genetic and epigenetic material of cells has undergone cancer mutation [ 2 ]. These mutations drive cells to continuously enter the cell cycle, avoid immune suppression, apoptosis, and mitosis, and contact suppression of cell growth, etc., and abnormal energy metabolism, hypoxia, and necrosis corresponding to continuous cell growth also induce changes in tumor angiogenesis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 OPGs in adults are rare, reported to be clinically aggressive, and often pathologically malignant. 6–8 Mishra et al reported that low-grade tumors accounted for only 22% of adult patients with OPG (≥50 years), whereas 96% of patients 5 to 9 years of age had low-grade gliomas. 9 …”
Section: Discussionmentioning
confidence: 99%
“…4,5 OPGs in adults are rare, reported to be clinically aggressive, and often pathologically malignant. [6][7][8] Mishra et al reported that low-grade tumors accounted for only 22% of adult patients with OPG ($50 years), whereas 96% of patients 5 to 9 years of age had low-grade gliomas. 9 MRI features of PAs in the optic nerve are hypointensity on T1weighted images, hyperintensity on T2-weighted images, and homogeneous gadolinium enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive genetic analyses of these complicated tumors are needed to aid with prognosis and treatment, particularly for sporadic cases of ONG which may exhibit an unpredictable clinical course. However, few studies exist, possibly reflecting difficulty in obtaining tissue in this anatomical location [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive genetic analyses of these complicated tumors are needed to aid with prognosis and treatment, particularly for sporadic cases of ONG which may exhibit an unpredictable clinical course. However, few studies exist, possibly reflecting difficulty in obtaining tissue in this anatomical location [9]. WES of the index patient revealed a somatic NF1 mutation, well-recognized to propagate ONG in patients with germline NF1 mutations, but with an unclear role in sporadic ONG.…”
Section: Discussionmentioning
confidence: 99%